Hybrid Breeding in Barley. Issue 3 (1st May 2013) - Mühleisen, Jonathan; Maurer, Hans Peter; Stiewe, Gunther; Bury, Paul; Reif, Jochen C.
ABSTRACT: Barley ( Hordeum vulgare L.) has been largely neglected in hybrid breeding research of autogamous cereals. The objectives of our study were (i) to study the amount of heterosis, (ii) examine the potential to predict hybrid performance based on midparent values or general combining ability (GCA) effects, and (iii) draw conclusions on the prospects for hybrid breeding in barley. Grain yield performance of 124 hybrids of six‐rowed winter barley, their 27 male and 38 female parental lines, as well as nine line and six hybrid varieties and one hybrid in registration was investigated in plot‐based multi‐environment trials. In a two‐stage analysis, best linear unbiased estimators and variance components of hybrids and parental lines were calculated. Midparent heterosis averaged 11.3%, with a range from 0.7 to 19.9%. Better‐parent heterosis was slightly lower with an average of 9.2%. Maximum commercial heterosis (i.e., the difference between the hybrid performance and the performance of the best line variety) was 7.6%, which clearly underlines the significance of hybrid barley breeding. Accuracy to predict hybrid performance was only moderate based on midparent values ( r = 0.46; P < 0.001) and GCA effects ( r = 0.38; P < 0.001). Consequently, there is a need for alternative approaches to predict hybrid performance in barley.